Financial Risks of Russian Oil Companies in Conditions of Volatility of Global Oil Prices - Chikunov, Sergey O.; Ponkratov, Vadim V.; Sokolov, Alexander A.; Pozdnyaev, Andrey S.; Osinovskaya, Irina V.; Ivleva, Marina I. (International Journal of Energy Economics and Policy, 2019)
The development of scientific approaches to assessing and diagnosing the financial risks of oil industry in the Russian Federation becomes a high priority task in conditions of high level of volatility in oil prices in the world energy market and preservation of sanctions regime. The article shows the main threats to financial stability of oil companies in Russia. Using cluster analysis, a system of indicators is proposed that determines the level of financial risk of oil companies in Russia. Based on the method of expert assessments and fuzzy sets, the classification of financial risk levels of oil industry is proposed. The integrated financial risk level of oil industry was calculated and scenarios of its development for 2018–2020 were forecast by means of regression modeling. The system of measures to improve the stability of oil companies and prevent functional financial risks is argued. The practical implementation of research results will be the basis for timely diagnosis of financial risks and qualitative development of preventive measures to neutralize them in the oil industry of Russia. Keywords: Oil Industry, Oil Companies, Financial Risks, Oil Prices, Financial Stability of Oil Industry JEL Classifications: Q43; Q41; G32; L52 DOI: https://doi.org/10.32479/ijeep.7358